2021
DOI: 10.14202/vetworld.2021.1929-1934
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance of Staphylococcus aureus isolated from raw cow and goat milk produced in the Tiaret and Souk Ahras areas of Algeria

Abstract: Background and Aim: Staphylococcus aureus is a leading cause of infection in both humans and animals. Most livestock strains have shown antibiotic resistance to the many molecules used in veterinary therapeutics. This study aimed to assess the resistance patterns of these bacteria, we carried out our study in the Tiaret and Souk Ahras areas of Algeria. Materials and Methods: We collected 116 samples of bovine and goat milk to detect S. aureus. We used a selective media to isolate the strains, followed by bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…This is nearly similar to a recent study from Sharkia Governorate, Egypt (20%) [ 28 ]. Other studies conducted elsewhere, however, have recently reported a higher S. aureus prevalence; in China (43.1%) [ 13 ], Algeria (33.33%) [ 12 ], and Turkey (37.32%) [ 29 ]. Variations from country to country and even from region to region in the same country may be because of different sample sizes, antibiotics in animal husbandry, and hygiene standards for dairy cows.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is nearly similar to a recent study from Sharkia Governorate, Egypt (20%) [ 28 ]. Other studies conducted elsewhere, however, have recently reported a higher S. aureus prevalence; in China (43.1%) [ 13 ], Algeria (33.33%) [ 12 ], and Turkey (37.32%) [ 29 ]. Variations from country to country and even from region to region in the same country may be because of different sample sizes, antibiotics in animal husbandry, and hygiene standards for dairy cows.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic sensitivity testing revealed that S. aureus isolates were resistant to penicillin and oxacillin and cefoxitin (32%), oxytetracycline (16%), and norfloxacin (16%), and antibiotic resistance genes, blaZ (32%) , tetK (16%) , and norA (16%),were detected in consistency with the phenotypic profile ( Tables 3 and 4 ). Several studies, in recent years, have reported multiple resistances of S. aureus to a wide range of antibiotics, including β-lactams [ 12 , 13 , 30 , 31 ]. Consequently, β-lactam antibiotics are no longer effective in treating S. aureus infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fresh milk contaminated with S. aureus and antibiotic resistance can result in toxic shock syndrome (Tamendjari et al 2021). Furthermore, S. aureus infections brought on by resistant strains are more challenging to treat than infections brought on by non-resistant strains, and the bacteria do not react well to treatments therein (Chambers and Deleo 2009).…”
Section: Introductionmentioning
confidence: 99%